CgATP synthase β subunit involved in the regulation of haemocytes proliferation as a CgAstakine receptor in Crassostrea gigas. Issue 123 (April 2022) - Yang, Ying; Qiao, Xue; Song, Xiaorui; Zhang, Dan; Yu, Simiao; Dong, Miren; Liu, Xiyang; Wang, Lingling; Song, Linsheng
Abstract: Astakine is considered as an endogenous cytokine-like factor of prokineticin homologue in invertebrate. Recently, an astakine homologue ( Cg Astakine) has been identified and characterized in oyster Crassostrea gigas . In the present study, a Cg ATP synthase β subunit was identified as the receptor of Cg Astakine in C. gigas . There was an ATP-synt_ab_N domain and an AAA domain in the Cg ATP synthase β subunit protein. The mRNA transcripts of Cg ATP synthase β subunit were detected in all tested tissues, with the highest expression level in hepatopancreas and gills, which was 109.11-fold ( p  < 0.01) and 97.21-fold ( p  < 0.01) of that in labial palps, respectively. After r Cg Astakine stimulation, the mRNA transcripts of Cg ATP synthase β subunit in agranulocytes and semi-granulocytes were significantly increased at 24 h (2.44-fold, and 9.01-fold of that in control group, p  < 0.01), and those in granulocytes were significantly increased at 6 h (1.83-fold, p  < 0.01), 12 h (1.92-fold, p  < 0.01) and 24 h (3.47-fold, p  < 0.01). The expression level of Cg ATP synthase β subunit protein in agranulocytes and granulocytes was also significantly increased after r Cg Astakine stimulation, which was 1.64-fold ( p  < 0.05) and 1.85-fold ( p  < 0.05) of that in control group, respectively, while there were no significant changes in semi-granulocytes. The immunofluorescence assay showed that Cg ATP synthase β subunit positive signals were mainly located on the membrane of haemocytes. The number of haemocytes with EdU positive signals was significantly increased after r Cg Astakine stimulation (2.04-fold of seawater group, p  < 0.01), while significantly decreased after the RNA interference (RNAi) of Cg ATP synthase β subunit, which was 0.28-fold of that in NC group ( p  < 0.01). Bio-layer interferometry (BLI) assay confirmed in vitro interaction between r Cg Astakine and r Cg ATP synthase β subunit. There results suggested that Cg ATP synthase β subunit acts as the receptor of Cg Astakine and plays important roles in Cg Astakine induced renewal of haemocytes in C. gigas . Highlights: An ATP synthase β subunit was identified from oyster, which interacted with Cg Astakine in vitro. Cg ATP synthase β subunit responsed to Cg Astakine stimulation with up-regulated expression mainly in granulocytes. The number of haemocytes with EdU positive signals was significantly decreased in Cg ATP synthase β subunit-RNAi oyster.